Determination of the tunneling time of particles through a double barrier - A. K. Zaichenko (Ядерна фізика та енергетика)
The method of calculation of the transmission coefficient and tunneling time of particles through a double barrier is proposed which takes into account the irreversibility of wave packets spreading. The resonance values of the transmission coefficient and tunneling time of neutrons through two barriers are calculated. The obtained value of tunneling time is compared with the experimental results.